Role of Serum Triglycerides in Development and Progression of Diabetic Nephropathy - Imran Ali Zaidi, Haleema Sajid, Sobia Niaz, Shamaila Doggar, Farouk Qamar Malik, Sana Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypercoagulation is hallmark complication of Diabetes mellitus where increased coagulability of blood manifests in the form of more clot formation. Type 2 Diabetes Mellitus is a longstanding metabolic abnormality indicated by elevated sugar values in blood and insulin resistance. Aim: To evaluate role and association of serum triglycerides levels in onset and progression of diabetic nephropathy. Materials: 120 patients are included in our study and cases are managed into 02 groups(60 patients each group). A Group: included diabetic cases without nephropathy B Group: included 60 diabetes patients with nephropathy The study data was then analyzed by software SPSS 21 number version. The Probability (P statistical Value) value of < 0.05 was decided as convincing number statistically. Results. The serum triglycerides levels were 159± 13 in A group and 210± 13 in the B group. The unpaired(independent) samples T- statistical test was utilized Using a two-tailed 0.05 criterion, the test showed remarkable difference between the two groups statistically (p value was < 0.05) in relation to serum triglycerides. Based on the inferences of the unpaired (independent sample) t- statistical test (p value was less than 0.05), we repudiated the null statistical hypothesis. Conclusion: Hypertriglyceridemia plays significant part in onset, development and progression of nephro-pathy in diabetic patients. Keywords: Hypertriglyceridemia, Diabetic Nephropathy, Diabetes Mellitus